The essential elements of health impact assessment and healthy public policy: a qualitative study of practitioner perspectives - Harris, Patrick John; Kemp, Lynn Amanda; Sainsbury, Peter (BMJ open, 2012)
Objectives This study uses critical realist methodology to identify the essential and contingent elements of Health Impact Assessment (HIA) and Healthy Public Policy (HPP) as operationalised by practitioners. Design Data collection—qualitative interviews and a workshop were conducted with HIA and HPP practitioners working in differing contexts. Data analysis Critical realist analytical questions identified the essential elements of HIA and HPP, the relationship between them, and the influences of public policy and other contingencies on the practice of both. Participants Nine interviews were conducted with purposively sampled participants working in Europe, USA and Australasia. 17 self-selected participants who worked in Europe, South East Asia and Australasia attended the workshop. Results The results clarify that HIA and HPP are different but mutually supporting. HIA has four characteristics: assessing a policy proposal to predict population health and equity impacts, a structured process for stakeholder dialogue, making recommendations and flexibly adapting to the policy process. HPP has four characteristics: concern with a broad definition of health, designing policy to improve people's health and reduce health inequities, intersectoral collaboration and influencing the policy cycle from inception to completion. HIA brings to HPP prediction about a policy's broad health impacts, and a structured space for intersectoral engagement, but is one approach within a broader suite of HPP activities. Five features of public policy and seven contingent influences on HIA and HPP practice are identified. Conclusions This study clarifies the core attributes of HIA and HPP as separate yet overlapping while subject to wider influences. This provides the necessary common language to describe the application of both and avoid conflated expectations of either. The findings present the conceptual importance of public policy and the institutional role of public health as distinct and important influences on the practice of HIA and HPP.